Hypertension among the Elderly in the Tzu Chi Flat, West Jakarta, Indonesia - Mey Lona Verawaty Zendrato; Veronika Fernanda Dua Hiko; Nurhasanah (Archives of Current Research International, 2024)
Aims: Hypertension is a cause of premature death in the world that should be prevented. As well as being the number 3 cause of death after stroke and tuberculosis in Indonesia. This study aims to get an overview of the blood pressure of the elderly in the tzu chi flat so that it can inform especially the elderly, accompanying families, health cadres and health workers so that they can make various efforts to anticipate the occurrence of hypertension, care and rehabilitation measures. Study Design: Cross sectional survey. Place and Duration of Study: Sample in this research is elderly in the Tzu Chi Flat, Jakarta between February – June 2022. Methodology: Quantitative research was used using the survey method with a cross-sectional approach which was conducted on 95 elderly people. This research was divided into 4 phases, namely the preparation phase, the implementation phase, the integration phase and the dissemination. Results: In the implementation, data collection was carried out, namely visual acuity measurements and interviews using a questionnaire where the results obtained were 35 elderly (36.8%) experiencing pre-hypertension. And as many as 38 elderly (40%) experienced hypertension in the age range of 60-74 years. Where 28 (73.7%) elderly hypertension is predominantly not working with (100%) having a low level of education. Conclusion: However, the elderly who have hypertension in the Tzu Chi Flat still have a high level of independence in carrying out their daily activities. Based on these results, it shows that the hypertension rate is strongly related to age, physical activity and level of education in the Tzu Chi flat. For this reason, there must be treatment that can be done, such as prevention and control of hypertension in the elderly, namely early detection which involves the role of the family and even health workers. Health workers can work together with integrated healthcare center cadres as the first line to reach the elderly (An extension of the hand) to increase the knowledge of the elderly about the health status of the elderly.